Microbiological and Geochemical Survey of CO2-Dominated Mofette and Mineral Waters of the Cheb Basin, Czech Republic - Krauze, Patryk; Kämpf, Horst; Horn, Fabian; Liu, Qi; Voropaev, Andrey; Wagner, Dirk; Alawi, Mashal (Frontiers in Microbiology, 2017)
The Cheb Basin (NW Bohemia, Czech Republic) is a shallow, neogene intracontinental basin. It is a non-volcanic region which features frequent earthquake swarms and large-scale diffuse degassing of mantle-derived CO2 at the surface that occurs in the form of CO2-rich mineral springs and wet and dry mofettes. So far, the influence of CO2 degassing onto the microbial communities has been studied for soil environments, but not for aquatic systems. We hypothesized, that deep-trenching CO2 conduits interconnect the subsurface with the surface. This admixture of deep thermal fluids should be reflected in geochemical parameters and in the microbial community compositions. In the present study four mineral water springs and two wet mofettes were investigated through an interdisciplinary survey. The waters were acidic and differed in terms of organic carbon and anion/cation concentrations. Element geochemical and isotope analyses of fluid components were used to verify the origin of the fluids. Prokaryotic communities were characterized through quantitative PCR and Illumina 16S rRNA gene sequencing. Putative chemolithotrophic, anaerobic and microaerophilic organisms connected to sulfur (e. g. Sulfuricurvum, Sulfurimonas) and iron (e. g. Gallionella, Sideroxydans) cycling shaped the core community. Additionally, CO2-influenced waters form an ecosystem containing many taxa that are usually found in marine or terrestrial subsurface ecosystems. Multivariate statistics highlighted the influence of environmental parameters such as pH, Fe2+ concentration and conductivity on species distribution. CO2-influenced waters form an ecosystem of which many taxa are usually found in marine or terrestrial subsurface ecosystems. The hydrochemical and microbiological survey introduces a new perspective on mofettes. Our results support that mofettes are either analogues or rather windows into the deep biosphere and furthermore enable access to deeply buried paleo-sediments.